Análisis y diseño de la cimentación superficial de una torre de alta tensión en líneas de transmisión - Caycho Alarcón, Franco Giovanni (2020)
This thesis work involve an analysis and design of two types of surface foundations used in electrical transmission towers based on international and national standards applied to the reality of the country. This study is applied to a 43.1m high transmission tower that is part of a project called "Línea de Transmisión 220 kV La Virgen - Caripa". About the design of the foundations, compression and turning verifications are made to define the geometry and size in order to respect the bearing capacity of the ground (1kg / cm2), in addition the foundation is designed by punching, cutting, bending and the verification by removal. A metal tower is modeled in the SAP2000 software, having previously defined all the loads in the structure to obtain the compression and tensile reactions at the base, with this reactions manual calculations are carried out for the different verifications and compared with the results obtained by the SAFE software when modeling the superficial foundations in this program, thus resulting in verification by compression being the determining factor for the geometry of the foundation in soils with low resistance. Finally, the types of surface foundations designed for the transmission tower are compared in terms of cost, being the footings the most economical type of foundation in comparison with a foundation slab and the structural plans of these surface foundations are presented.